Odorant Binding Proteins and Chemosensory Proteins in Episyrphus balteatus (Diptera: Syrphidae): Molecular Cloning, Expression Profiling, and Gene Evolution. Issue 4 (8th August 2020) - Jia, Hui-Ru; Niu, Lin-Lin; Sun, Yu-Feng; Liu, Yong-Qiang; Wu, Kong-Ming
Abstract: Aphidophagous syrphids (Diptera: Syrphidae) are important insects in agroecosystems for pollination and biological control. Insect chemoreception is essential for these processes and for insect survival and reproduction; however, molecular determinants is not well understood for these beneficial insects. Here, we used recent transcriptome data for the common hoverfly, Episyrphus balteatus, to characterize key molecular components of chemoreception: odorant-binding proteins (OBPs) and chemosensory proteins (CSPs). Six EbalCSPs and 44 EbalOBPs were cloned from this species, and sequence analysis showed that most share the characteristic hallmarks of their protein family, including a signal peptide and conserved cysteine signature. Some regular patterns and key conserved motifs of OBPs and CSPs in Diptera were identified using the online tool MEME. Motifs were also compared among the three OBP subgroups. Quantitative real-time PCR (qRT-PCR) showed that most of these chemosensory genes were expressed in chemosensory organs, suggesting these genes have chemoreceptive functions. An overall comparison of the Ka/Ks values of orthologous genes in E. balteatus and another predatory hoverfly species to analyze the evolution of these olfactory genes showed that OBPs and CSPs are under strong purifying selection. Overall, our results provide a molecular basis for further exploring the chemosensory mechanisms of E. balteatus, and consequently, may help us to understand the tritrophic interactions among plants, herbivorous insects, and natural enemies.